ANALYSIS OF ORAL HEALTH AND QUALITY OF LIFE OF GROUPS OF PATIENTS WITH TYPE 2 DIABETES AND CHRONIC KIDNEY DISEASE - Umid Golibovich Nusratov (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Recent advances in the study of the mechanisms of development of type 2 diabetes have contributed to the development of fundamentally new views on the genesis of the disease and its complications. Our goal is a comparative analysis of the assessment of quality of life in patients with type 2 diabetes mellitus complicated by chronic kidney disease after the use of orthopedic dental treatment. Analysis of questionnaires showed that the quality of life of patients with partial absence of teeth was reduced to a varying degree in all groups of patients. Summarizing the results of the study, we can conclude that the correct deontological approach using the developed recommendations for the collection of anamnesis will facilitate understanding by the dentist of the algorithms and methods of treating the patient and help to improve the quality of prosthetics and further rehabilitation.